1978
DOI: 10.1136/bmj.1.6106.145
|View full text |Cite
|
Sign up to set email alerts
|

Immediate heart-rate response to standing: simple test for autonomic neuropathy in diabetes.

Abstract: Summary and conclusionsThe immediate heart-rate response to standing was measured in 22 normal controls and 25 patients with diabetes, 15 of whom had autonomic neuropathy. The response in the controls and patients without autonomic neuropathy was characteristic and consistent, with tachycardia maximal at around the 15th beat and relative bradycardia maximal at around the 30th beat. The diabetics with autonomic neuropathy, however, showed a flat response. In three controls the response was abolished with intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
189
1
22

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(217 citation statements)
references
References 9 publications
5
189
1
22
Order By: Relevance
“…We must acknowledge that the exact pathophysiological correlate of ∆HR is unknown, and given the methods used in our study, it is likely that we assessed neither the maximum baroreflex‐mediated rise in HR nor the nadir of the relative bradycardia thereafter. Rather, our measurement likely reflects an average HR throughout this period of HR dynamics after getting up or even the more or less stable HR that is established after ~2 minutes at least in healthy subjects 10. Still, we assume that ΔHR as assessed in the present study reflects the integrity or defect, respectively, of the mechanisms responsible for an increased sympathetic outflow to the heart after a person gets up.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…We must acknowledge that the exact pathophysiological correlate of ∆HR is unknown, and given the methods used in our study, it is likely that we assessed neither the maximum baroreflex‐mediated rise in HR nor the nadir of the relative bradycardia thereafter. Rather, our measurement likely reflects an average HR throughout this period of HR dynamics after getting up or even the more or less stable HR that is established after ~2 minutes at least in healthy subjects 10. Still, we assume that ΔHR as assessed in the present study reflects the integrity or defect, respectively, of the mechanisms responsible for an increased sympathetic outflow to the heart after a person gets up.…”
Section: Discussionmentioning
confidence: 85%
“…Second, we studied a population with a high proportion of patients on β‐blocker therapy, and the effect of β‐blocker therapy on ΔHR is unknown. An early pathophysiological study has revealed that the above‐described HR response to standing is under vagal control 10. However, adjustment for baseline β‐blocker dosage did not alter the results (data not shown), and there was no interaction between baseline β‐blocker use and the association between ΔHR and outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The initial cardio accelerator is an exercise reflex, while the subsequent tachycardia and bradycardia are baroreflex mediated. The 30:15 ratio [RR interval at beat 30/RR interval at beat 15], serves as index of cardiovagal function [14,15]. When the ratio is 1 or less, vagal damage is probably present.…”
Section: Discussionmentioning
confidence: 99%